Preliminary characteristics of the children in age 3-7 years based on examinations carried for two years - Wich, Jerzy (Anthropological Review, 1976)
The purpose of this research is to asses physical development of children with various somatotypes in the age 3-7 years in order to establish new, more individualized developmental norms. These norms will be constructed with regard to age, sex, constitution and, to a certain extent, also with heritable properties. The examinations are carried on two groups: children from very good and poor living conditions in order to estimate influence. of environment on physical development. In this preliminary report only 9 among 26 observed somatic characters are presented for a group of 202 boys and 279 girls examined in 1972-73. The boys as a rule have higher mean values of characters than the girls. Rate of growth in the investigated period of life is even, not showing varying intensity throughout separate years. Comparison with a cross-sectional material collected in approximately same time in Lublin has shown serious differences between children from this town and their contemporaries from Wrocław. Moreover unequal sexual dimorphism became visible in both samples: smaller in Wrocław and larger in Lublin. If it were not random event it could be suggested that in less differentiated environment (Wrocław) sexual dimorphism diminishes s on the other hand it increase in differentiated environment (Lublin).